Penerapa Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Konsep Alat Optik Di Kelas VIII SMP Swasta Gane Raya Kabupaten Halmahera Selatan - Diana Kode-Kode (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2023)
This research aims to improve the learning outcomes of students in class VIII Gane Raya Private Middle School through the application of the Project Based Learning Learning Model. The research method used was qualitative where the research was conducted at Gane Raya Private Middle School Class VIII, with a total of 11 students. Sources of data come from teachers and students. Research data collection techniques were carried out using observation sheets on the implementation of learning models and test questions for learning. The data obtained were analyzed by descriptive qualitative. Based on the results of research in class VIII at Gane Raya Private Middle School, South Halmahera Regency, on the learning achievement test from cycle 1 to cycle II, there was an increase of 39%. Whereas The results showed that the average score of students in cycle I was 45 while in cycle 2 it was 81, so there was an increase of 39%. It can be said that the Project Based Learning Learning Model can improve student learning outcomes on the concept of optical devices at Gane Raya Private Middle School